Cardioprotective effect of Trichopus zeylanicus against myocardial ischemia induced by isoproterenol in rats - Sivanandham Velavan; S. Selvarani; A. Adhithan (Bangladesh Pharmacological Society, 2009)
The cardioprotective effects of Trichopus zeylanicus leaves against isoproterenol-induced myocardial ischemia was studied. Wister strain rats were pretreated with T. zeylanicus leaves (500 mg/kg body weight) for 28 days and then intoxicated with isoproterenol (20 mg/100 g, i.p. for 2 consecutive days). Cardioprotection was assessed by estimating plasma and heart aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, and creatine phosphokinase. Troponin T was estimated in serum, the levels of thiobarbituric acid reactive substances (TBARS), reduced glutathione (GSH) were analyzed in heart and plasma. In isoproterenol-treated group, shrinkage of cardiac markers in plasma and elevated lipid peroxidation where accompanied by decreased content of reduced glutathione in heart and plasma. The prior administration of T. zeylanicus significantly (p < 0.001) prevented the isoproterenol-induced alterations and restored the cardiac markers. These findings indicate the cardioprotective activities of T. zeylanicus during isoproterenol-induced myocardial ischemia.